2012
DOI: 10.1097/tp.0b013e318241987c
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Transplantation Search Filters for PubMed, Ovid Medline, and Embase

Abstract: These kidney transplantation filters can now be used in Medline and Embase databases to improve clinician searching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…Building on the same concepts our group has used to create novel high performance search filters for general nephrology and renal transplantation [15,18], we have succeeded in developing and validating search filters for glomerular disease that are highly sensitive and specific. All filters achieved a balance of at least 93.8% sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on the same concepts our group has used to create novel high performance search filters for general nephrology and renal transplantation [15,18], we have succeeded in developing and validating search filters for glomerular disease that are highly sensitive and specific. All filters achieved a balance of at least 93.8% sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, topic-based search filters have started to emerge [15-17]. Within the area of nephrology, search filters already exist to retrieve renal information and articles relevant to kidney transplantation [15,18]. However, none of these filters were designed to enhance retrieval of articles relevant only to glomerular disease.…”
Section: Introductionmentioning
confidence: 99%
“…This complements our work done to develop information filters for kidney transplantation (24) and general nephrology (3). Better access to dialysis information is important because dialysis patients have high morbidity and mortality, with high costs to health care systems.…”
Section: Strengths and Limitationsmentioning
confidence: 60%
“…By embedding the best evidence about searching into a predefined strategy, search filters seek to minimise variations and deficits in individuals’ searching knowledge and skills and can prevent ‘reinventing the wheel’ for commonly sought searches. Several studies have demonstrated search filter superiority in direct head‐to‐head comparisons with clinician subject specialist searches (Damarell & Tieman, ; Garg et al., ; Hildebrand et al., , ; Iansavichus et al., , , ; Lee, Iansavichus et al., ).…”
Section: Introductionmentioning
confidence: 99%